Contesting Connectivity: India’s Discourse on CPEC and Its Impact on Sino-Indian Strategic Engagement - Muhammad Ahmad Khan; Sardar Jehanzaib Ghalib (BTTN Journal, 2025)
India has been very critical of Chinese investment in South Asia, especially in Pakistan, citing concerns about its sovereignty and the growing influence of China through the Belt and Road Initiative (BRI). Indian media, in synergy with official claims, has raised concerns regarding the China-Pakistan Economic Corridor (CPEC) by a false argument that the project key artery passes through a disputed region of Gilgit Baltistan, only to minimize the rising Chinese influence in the region. . . . In this regard, the study focuses on three main questions: the impact of Indian media discourse on Sino-Indian relations, India’s rationale behind the proliferation of anti-CPEC discourse, and the implications on Sino-Indian relations as a result of India’s continuous opposition to CPEC. To find answers to these research questions, the study employs the discourse analysis framework, which analyzes the Indian media content in line with New Delhi’s policy line concerning CPEC since the project’s announcement.